О происхождении двоевластия у хазар и обстоятельствах их обращения в иудаизм - Цукерман, К. (Материалы по археологии, истории и этнографии Таврии, 2002)
Недавний всплеск интереса к хазарской проблематике, ярко проявившийся в появлении большого числа важных археологических исследований, не менее заметен в вопросах политической, социальной и религиозной истории хазар, изучаемых в основном на базе письменных источников. Помимо прочих достижений в этой области, недавние исследования проливают свет на проблемы властных структур Хазарского государства и природы хазарского двоевластия. The Arab geographers and historians of the late ninth and the tenth century provide a rather static view of Khazaria’s political structure with, at the top, a ceremonial sacral ruler, the kaghan, who exercises no real power, and his “deputy”, the shad (or the beg or the king), who rules the state and commands the troops while paying the kaghan a symbolic respect. This picture of what came to be known as the Khazar diarchy had been traditionally projected by scholars deep into the past, back -o the origins of the Kaghanate, and perceived as a basic structural feature of the Khazar polity, rooted in Turkic tradition. Recent studies by D.Ludwig and A.RNovosel’cev have shown, however, that the early references to the Khazars attribute all power to the kaghan and reveal no trace of any kind of diarchy before the ninth century. The ninth-tenth-century data is thus only valid for its own time and should not be projected in the past. This paper situates the roots of change in the second third of the ninth century and tries to explain the intricate interplay of external and internal pressures at those crucial crossroads of the Khazar history.